Emotional impact of compassionate extubation on respiratory therapists and nurses: A pilot study - Ramandeep Kaur; Elaine Chen; Anam S. Faizi; Vivien Joy Lamadrid; David L. Vines; J. Brady Scott (Canadian Journal of Respiratory Therapy, 2022)
Background: Compassionate extubation (CE) refers to withdrawing mechanical ventilation and allowing a patient to die peacefully at the end of life. The primary objective of this pilot study was to quantify the emotional impact of CE on Respiratory Therapists (RT) and Registered Nurses (RNs). Methods: This pilot survey was conducted between March and April 2021 at an academic medical center among RTs and RNs. It included questions on participants’ demographics, work characteristics, and Impact of Events (IES) scale to assess the subjective stress caused by CE. Data were analyzed using descriptive and χ2 statistics. Results: Among 20 participants, 18 (90%) were females, 12 (60%) were in the 20–40-year age group, 12 (60%) were RTs, and 8 (40%) RNs. Around 15 (75%) participants worked day shifts with a weekly average of 3–4 shifts, and 14 (70%) performed/observed CE within 1 month before taking this survey. CE performed/observed in a month was ≤2 among 15 (75%) and 3–5 among 4 (20%) participants. Mean total IES score was 16.7 (12.3) among all participants representing 7 (35%) having low, 6 (30%) moderate, and 7 (35%) high emotional impact when performing CE. Risk of developing post-traumatic stress disorder (PTSD) was present in 6 (30%) participants. A significantly higher number of participants in the low impact group were satisfied with the institutional CE process (p = 0.043) than those in the medium/high impact group. Conclusion: This pilot study findings reveal that RTs and RNs experience moderate to high levels of subjective stress when performing CE. One-third of the survey participants were at risk of developing PTSD.